Variation of Soil Temperatures in Ogotoruk Valley, Alaska - Weedfall, Robert O. (ARCTIC, 1963)
The study on which this paper is based was made under the auspices of the U.S. Atomic Energy Commission. Its purpose was to provide sufficient meteorological and climatological information about Ogotoruk Valley so that any changes in the biosphere and ecology of the valley after the proposed atomic excavation of the harbour could be more easily related to variations in the climate rather than to radiation aftereffects. . The micrometeorological station network (Fig. 1) extended from the mouth of Ogotoruk Creek on the Chukchi Sea up to 6.5 miles inland, and the stations were spread on both sides of the 2-mile-wide valley. Specialized instrumentation was necessary only for the soil thermometers and pyrheliographs. The soil thermometers were of the hydrocarbon-in-steel type, manufactured by the Palmer Thermometer Company and permitted daily reading of the maximum and minimum temperature since the preceding observation. They were clamped between radiation shields for measuring air temperatures at 5 and 50 cm. above the ground and were buried at 5-, 10-, 20-, and 50-cm. depths in the soil at each of the stations. Solar radiation was measured by pyrheliographs with 7-day clockworks furnished by the Belfort Instrument Company. Almost two full summers of weather and soil temperature data were collected during 1960 and 1961. .